(untitled) (London Journal of Research In Humanities and Social Sciences, 2023)
Waste generation occurs in almost all sectors of society including the oil and gas sector. The inability to properly manage waste causes environmental havoc, especially in the oil and gas industries. Notwithstanding the economic factors in the country, the operational activities within the oil and gas sector contribute to water pollution, air pollution, water bodies contamination, shortage of land for waste disposal, and potential financial liabilities. This study aimed to critically examine the waste management practices within the Oil and Gas Companies in the Western Region using Schlumberger and Zoil Services Limited as cases. The waste management theory, environmental economics theory, and sustainability theory informed this study. The quantitative research approach and survey design were relied upon in this study. The population: this study consisted of a selected staff of Schlumberger Base inside Takoradi Port and Zoil Services Limited at Inchaban in the Western Region of Ghana. Purposive and simple random sampling methods were used to select 83 respondents for the study. Frequencies, percentages, means, standard deviation, and an independent samples t-test were used for data analysis. Even though the companies are aware of the types of waste and have different facilities to manage these wastes, some of the facilities were obsolete which cannot ensure effective management of waste. It is recommended that the Management of the two companies should invest in the maintenance, redesign, and re-engineering of their facilities to fit modern waste treatment methods and procedures.